Evaluation of indoor environment conditions in offices located in buildings with large glazed areas - Šeduikytė, Lina; Paukštys, Valdas (Journal of Civil Engineering and Management, 2008)
The field study was carried out during the heating season in two Lithuanian office buildings with large glazed areas. The methodology was prepared for evaluating indoor microclimate parameters while using objective and subjective evaluation. The results show that the average temperature in all tested offices was in the range of optimal zones, but in some offices the average temperature was not in compliance with the recommended temperature for offices. During the subjective evaluation, respondents working in these offices identified complains because of too high temperatures, stuffy air and irritation in eyes. The average relative humidity measured in all tested offices was not in compliance with the optimal requirements. Such SBS symptoms as irritation in eyes, cough and dry skin of the hands were identified as the most frequent symptoms in the second tested building. Main indoor microclimate problems arising in buildings with large glazed areas were related to overheating indoor spaces because of the direct sun and improper ventilation.Biuro pastatų, turinčių didelius įstiklintus plotus, mikroklimato sąlygų vertinimasSantrauka. Straipsnyje nagrinėjamos patalpų mikroklimato sąlygos pastatuose esančiuose biuruose, turinčiuose didelius įstiklintus plotus. Didelių skaidrių atitvarų plotų įrengimas pastatuose ne tik didina energijos sąnaudas pastatams šildyti, vėsinti ir orui kondicionuoti, bet ir sukuria mikroklimato sąlygas, kuriose dirbantys žmonės dažnai patiria šiluminį diskomfortą, nors aplinkos parametrai atitinka normų reikalavimus. Natūriniams patalpų mikroklimato tyrimams sukurta patalpų mikroklimato tyrimo metodika, kuri sieja objektyvius ir subjektyvius tyrimo metodus patalpų sąlygoms optimaliai įvertinti. Patalpų mikroklimato sąlygos tiksliausiai įvertinamos pagal patalpų mikroklimato parametrų matavimo, papildyto subjektyvaus mikroklimato sąlygų įvertinimu, apibendrintos analizės rezultatus.Reikšminiai žodžiai: biuro patalpų mikroklimatas, objektyvus ir subjektyvus įvertinimas, stikliniai fasadai.First Published Online: 14 Oct 2010